A Geriatric Assessment Intervention to Reduce Treatment Toxicity Among Older Adults With Advanced Lung Cancer: A Subgroup Analysis From a Cluster Randomized Controlled Trial - Presley, Carolyn J.; Mohamed, Mostafa R.; Culakova, Eva; Flannery, Marie; Vibhakar, Pooja H.; Hoyd, Rebecca; Amini, Arya; VanderWalde, Noam; Wong, Melisa L.; Tsubata, Yukari; Spakowicz, Daniel J.; Mohile, Supriya G. (Frontiers in Oncology, 2022)
Introduction: More older adults die from lung cancer worldwide than breast, prostate, and colorectal cancers combined. Current lung cancer treatments may prolong life, but can also cause considerable treatment-related toxicity. Objective: This study is a secondary analysis of a cluster-randomized clinical trial which evaluated whether providing a geriatric assessment (GA) summary and GA-guided management recommendations can improve grade 3-5 toxicity among older adults with advanced lung cancer. Methods: We analyzed participants aged >70 years(y) with stage III & IV (advanced) lung cancer and >1 GA domain impairment starting a new cancer treatment with high-risk of toxicity within the National Cancer Institute’s Community Oncology Research Program. Community practices were randomized to the intervention arm (oncologists received GA summary & recommendations) versus usual care (UC: no summary or recommendations given). The primary outcome was grade 3-5 toxicity through 3 months post-treatment initiation. Secondary outcomes included 6-month (mo) and 1-year overall survival (OS), treatment modifications, and unplanned hospitalizations. Outcomes were analyzed using generalized linear mixed and Cox proportional hazards models with practice site as a random effect. Trial Registration: NCT02054741. Results & Conclusion: Among 180 participants with advanced lung cancer, the mean age was 76.3y (SD 5.1), 39.4% were female and 82.2% had stage IV disease. The proportion of patients who experienced grade 3-5 toxicity was significantly lower in the intervention arm vs UC (53.1% vs 71.6%, P=0.01). More participants in the intervention arm received lower intensity treatment at cycle 1 (56.3% vs 35.3%; P<0.01). Even with a cycle 1 dose reduction, OS at 6mo and 1 year was not significantly different (adjusted hazard ratio [HR] intervention vs. UC: 6mo HR=0.90, 95% CI: 0.52-1.57, P=0.72; 1 year HR=0.89, 95% CI: 0.58-1.36, P=0.57). Frequent toxicity checks, providing education and counseling materials, and initiating direct communication with the patient’s primary care physician were among the most common GA-guided management recommendations. Providing a GA summary and management recommendations can significantly improve tolerability of cancer treatment among older adults with advanced lung cancer.